A Kinematic Analysis of Gait during Obstacle Crossing in Middle-Aged Women - Khoshjamal Fekri, Sara; Tabatabai Ghomsheh, Farhad; Fatahi, Ali (Journal of Clinical Physiotherapy Research, 2024)
Introduction: Due to the significant risk of falls caused by overcoming obstacles, extensive research has focused on lower extremity movements to develop fall prevention strategies. So this study was conducted to identify kinematic analysis of gait during obstacle crossing in middle-aged women. Materials and Methods: The study population consisted of healthy middle-aged women aged 55 to 64 years old from the city of Tehran. The minimum sample size was determined to be 24 individuals using G-power software. Angles of lower limb joints were collected using movement analysis cameras during normal gait and obstacle crossing and F point was measured which is when big toe of one’s left foot is at the greatest vertical distance from the ground. Paired-Sample T-Test was used with SPSS software version 22 at significant level of P≤0.05 for further statistical analysis. Results: At F point, the ankle and knee joint angles of both the right and left legs decreased significantly when crossing the obstacle compared to normal gait. In addition, Fpoint analysis showed a significant decrease in the hip joint angle of the right leg and a significant increase in the hip joint angle of the left leg. Conclusion: The observed kinematic changes indicate that obstacle navigation involves complex motor adjustments necessary to maintain balance and stability. Therefore, training and rehabilitation programs should address these adaptations by incorporating exercises to improve joint angles and minimize the risk of falls.